Application of Correction Procedures for Some Systematic Measurement Errors to Rainfall Intensity Data of a Rain Gauge in Budapest - Rácz, Tibor (Periodica Polytechnica Civil Engineering, 2021)
The rainfall intensity measurement has a 150 years long history. In the first period of data recordings, the siphoned recording precipitation gauge (pluviographs), or siphoned rainfall writers (SRW), later, the tipping bucket gauges (TBG) were widely used. The systematic errors of these instruments resulted in lower intensity values for long periods. These errors were compensated sporadically. Most of the inaccurate data can be found in the high rainfall intensity range. Some of these data can be found in extracted, aggregated versions only, and the original measurement data is no longer available. These kinds of inherited systematic errors can be corrected. The fixing of siphoning error of SRWs and the supplementary correction of long sampling period data of TBG devices can be a suitable method for the elimination of these issues. In this paper, the application of these two methods is shown in a case study to point out the magnitude and effect of these errors on the IDF curves. The case study on the use of the before-mentioned correction procedures is performed on the rainfall data of the Budapest-Belterület (Budapest City) rainfall station, using data series spanning 105 years. These corrections show that the earlier IDF curves can show 5–10% lower intensities, mainly in the short and low return frequency rainfalls. The result of these kinds of corrections can be significant for the climate change investigations or in the re-evaluation of the elder IDF curves.